Pembelajaran Pecahan dengan Menggunakan Manik Susun - Kiki Rizkiah Pertiwi; Zulkardi Zulkardi; Darmawijoyo Darmawijoyo (JRPM (Jurnal Review Pembelajaran Matematika), 2017)
This study aimed to design a learning path which can help students to understand fractions based on Pendidikan Matematika Realistik Indonesia (PMRI) approach. The subject is 30 students of 4th grade of PP Qodratullah Langkan. Method of this research is design research, Hypothetical Learning Trajectory (HLT) developed from learning activity series using context stacked beads. The implementation of this research in 3 stages: preparing the design experiment, conducting the learning (the design experiment), and retrospective analysis in order to contribute to Local Instruction Theory support to students in studying fractions. The designed Hypothetical Learning Trajectory (HLT) is then compared to Actual Learning Trajectory (ALT) students during the learning to analyze whether students learn or not from what has been designed in the learning sequence. A retrospective analysis of the implementation of learning suggests that the use of the stacking bead context can help students understand fractions.